Avaliação do nível da aplicação da NR-18 nos canteiros de obras da cidade de Tucuruí-PA - CARVALHO, Regiana Barbosa (2018)
Concern for safety is not a recent topic of old had already been reports of poor condi-tions in which work activities were performed. Conditions professionals subjected to various health problems or accidents. In the municipality of Tucuruí, located in Para State, entrepre-neurs, business owners and technical managers, culture is not requiring the use of safety equipment and educate employees or their use. The lack of concern with health and safety of the employee, a fundamental part in the production process, has shown a cruel and bitter reali-ty in the construction site, in the high number of accidents and diseases. Given the neglect aims to diagnose the actual working conditions on construction sites in the city. The objective of this study was to analyze the application of the requirements set out in Regulatory Standard No. 18 through questionnaires in eight works in the city. Besides the use of questionnaires aimed to employees and entrepreneurs. Before the analysis obtained from the questionnaires, it was concluded that 66.8% of the items on the checklist required by NR-18 are not met in the works visited, thus making the construction industry in the city more vulnerable to acci-dents at work can lead to death of the employee.Given the situationof theconstruction sitesof the city ofTucuruítoproposethe application of NR-18, withpartnershipsbetween universitie-sand local companiesas well asprofessional qualificationand increasedperformance of theDRT.